2007
DOI: 10.1152/jn.00788.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cortical fMRI Activation to Sequences of Tones Alternating in Frequency: Relationship to Perceived Rate and Streaming

Abstract: Wilson EC, Melcher JR, Micheyl C, Gutschalk A, Oxenham AJ. Cortical fMRI activation to sequences of tones alternating in frequency: relationship to perceived rate and streaming. J Neurophysiol 97: 2230-2238, 2007. First published January 10, 2007 doi:10.1152/jn.00788.2006. Human listeners were functionally imaged while reporting their perception of sequences of alternating-frequency tone bursts separated by 0, 1/8, 1, or 20 semitones. Our goal was to determine whether functional magnetic resonance imaging (fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
66
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 36 publications
15
66
2
Order By: Relevance
“…Instead, the changes are likely attributable to the ⌬f 0 -related differences in the temporal properties of the A and B tones. This dependence on temporal rather than spectral differences between A and B represents a crucial difference compared with previous imaging studies of streaming, all of which have used repeating sequences of pure tones (Gutschalk et al, 2005;Snyder et al, 2006;Wilson et al, 2007) or complex tones with gross spectral differences (Deike et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Instead, the changes are likely attributable to the ⌬f 0 -related differences in the temporal properties of the A and B tones. This dependence on temporal rather than spectral differences between A and B represents a crucial difference compared with previous imaging studies of streaming, all of which have used repeating sequences of pure tones (Gutschalk et al, 2005;Snyder et al, 2006;Wilson et al, 2007) or complex tones with gross spectral differences (Deike et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In fMRI, auditory cortical activation increased with increasing difference in f 0 in the present study, just as activation increased with increasing frequency difference in pure-tone paradigms (ABAB) . A mechanism previously proposed to underlie the increases in cortical activity seen in pure-tone studies is neural "adaptation" or "forward suppression" in which (1) the neural response to one tone suppresses the responses to subsequent tones, and (2) as successive tones are made increasingly different in frequency (or the time interval between tones is increased), the degree of suppression decreases (Gutschalk et al, 2005;Wilson et al, 2007). This frequency-selective forward suppression model maps straightforwardly to the data of the present study if it is assumed that the strength of suppression in some auditory cortical neurons depends on the f 0 difference between tones (i.e., is f 0 selective).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies exploring the neural correlates of streaming based on pitch have found either no difference in activation between the left and right hemispheres, or activation primarily in the right hemisphere (Cusack, 2005;Gutschalk et al, 2005Gutschalk et al, , 2007Snyder et al, 2006;Wilson et al, 2007). In contrast, Deike, Gaschler-Markefski, Brechmann, and Scheich (2004) and Deike, Scheich, and Brechmann (2010) found activation primarily in the left hemisphere when subjects were asked to segregate A from B tones continuously in sequences where the tones differed in timbre or in pitch.…”
Section: H Brain Mechanisms Underlying Streamingmentioning
confidence: 99%